Hey there! Sign in to join this conversationNew here? Join for free
    • Thread Starter
    Offline

    12
    ReputationRep:
    The function f(x) is defined by f(x)=x^2-3

    a) Find f^-1(x) in similar terms:

    Let y=f(x)

    y=x^2-3
    y+3=x^2
    x=(y+3)^0.5

    Therefore, f^-1(x)=(x+3)^0.5

    b) Find values of x such that f(x)=f^-1(x)

    I can't do this, any help would be appreciated.

    The textbook says When f(x)=f^-1(x)

    f(x)=x

    I don't understand this.
    Offline

    2
    ReputationRep:
    (Original post by Deep456)

    The textbook says When f(x)=f^-1(x)

    f(x)=x

    I don't understand this.
    Imagine you're sketching the graph of y=f(x) then on the same axes, you're sketching y=f^-1(x). You should find that the two curves are reflections of each other in the line y=x. This is a property of inverse functions that you would have learned before.

    Solving f(x)=f^-1(x) means finding where the two curves cross. They can only cross each other at the y=x line, hence if f(x)=f^-1(x) then f(x)=x.
    • Thread Starter
    Offline

    12
    ReputationRep:
    (Original post by ttoby)
    Imagine you're sketching the graph of y=f(x) then on the same axes, you're sketching y=f^-1(x). You should find that the two curves are reflections of each other in the line y=x. This is a property of inverse functions that you would have learned before.

    Solving f(x)=f^-1(x) means finding where the two curves cross. They can only cross each other at the y=x line, hence if f(x)=f^-1(x) then f(x)=x.
    Does that also mean f^-1(x)=x?

    Also if you weren't using this way and doing:

    x^2-3=(x+3)^0.5

    How would you go about it?
    Offline

    2
    ReputationRep:
    (Original post by Deep456)
    Does that also mean f^-1(x)=x?
    Yes. But in this case it's easier to use the result f(x)=x because in the next line of workings, you get a quadratic to solve which is fairly straightforward.
    Also if you weren't using this way and doing:

    x^2-3=(x+3)^0.5

    How would you go about it?
    Square both sides to give x^4-6x^2+9=x+3 hence x^4-6x^2-x+6=0. Then you'd have to solve that by guessing factors. (x-1) and (x+2) are factors that can be obtained here. Then you would divide the polynomial by (x-1) and by (x+2) to get a quadratic, then solve the quadratic to get two more factors.

    In total, this will give you four solutions to x^4-6x^2-x+6=0. However since earlier we squared both sides, some of those solutions would be not what we want, hence we would have to substitute each of the four possible solutions back in to f(x)=f^-1(x) to see if they fit.

    As you can see, it's a lot easier to use the f(x)=x method.
    • Thread Starter
    Offline

    12
    ReputationRep:
    Thanks.
 
 
 
Poll
Do you agree with the PM's proposal to cut tuition fees for some courses?
Useful resources

Make your revision easier

Maths

Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

Equations

How to use LaTex

Writing equations the easy way

Student revising

Study habits of A* students

Top tips from students who have already aced their exams

Study Planner

Create your own Study Planner

Never miss a deadline again

Polling station sign

Thinking about a maths degree?

Chat with other maths applicants

Can you help? Study help unanswered threads

Groups associated with this forum:

View associated groups

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

Write a reply...
Reply
Hide
Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.